THE MODERATING ROLE OF PROFITABILITY ON CAPITAL STRUCTURE AND STOCK PRICES: EVIDENCE FROM INDONESIA - Andi Kusuma Negara (Dynamic Management Journal, 2026)
This study examines the moderating role of profitability on the relationship between asset structure and capital structure on stock prices in food and beverage sub-sector companies listed on the IDX during 2019–2023. The novelty lies in using profitability as a moderating variable, rarely tested in this post-pandemic sector, and integrating three financial variables in one model examining direct and interaction effects simultaneously. The population covers all related sub-sector companies, with 21 samples selected through purposive sampling, yielding 105 observations. The analysis employs panel data regression with Fixed Effect Model (FEM) after Chow and Hausman tests, using Eviews 13. The results show capital structure (DER) has a negative significant effect on stock prices, while asset structure has no significant effect. Profitability (ROE) has a positive significant effect. The main finding, which also constitutes the novelty, is that profitability significantly moderates the influence of both asset structure and capital structure on stock prices, indicating that earnings performance reinforces market responses to financing and investment policies. The implications suggest that investors should consider profitability as a reinforcing signal, and management should balance debt usage and profitability efficiency to enhance firm value.